Managerial ownership and firm performance: The influence of family directors and non-family directors - Kamardin, Hasnah (Emerald Group Publishing Limited, 2014)
Purpose The main purpose of the study is to examine the influence of family directors on the firm performance of public listed companies (PLCs) in Malaysia. This study provides empirical evidence on the agency problems between controlling shareholders and minority interests in the concentrated ownership setting. Design/methodology/approach Samples of the study are 112 PLCs in year 2006. Two measures of firm performance are used: return on assets (ROA) and Tobin’s Q. Managerial ownership refers to the percentage shareholdings of executive directors with direct and indirect holdings. It was further categorized into family ownership and non-family ownership.Findings In relation to ROA, managerial ownership is found positively significant. The results also show that the positive relationship between managerial ownership is contributed by the managerial-non-family ownership. In relation to Tobin’s Q, the results show a U-shape with turning point at 31.38% for managerial ownership and 28.29% for the managerial-family ownership. The results found significant and positive relationships between managerial ownership and both measures of firm performance which indicates that managerial ownership and family ownership yield greater efficiency.Research implications The study highlights the effects of corporate governance on ROA and Tobin’s Q are somewhat different. It provides some evidence on the need to use appropriate measure of firm performance. The significant relationship supports the argument of Chami (1999), Fama and Jensen (1983), and DeAngelo and DeAngelo (1985) and empirical evidence of Lee (2004) that family ownership enhances monitoring activities.Originality/value Differentiating the types of managerial ownership into family and non-family categories enriches our knowledge about who actually contributes to the improved performance.